The economics of geological CO2 storage and leakage - Bob van der Zwaan; Reyer Gerlagh (Fondazione Eni Enrico Mattei (FEEM), 2008)
The economics of CO2 capture and storage in relation to the possibility of significant leakage of CO2 from geological reservoirs once this greenhouse gas has been stored artificially underground will be among the main determinants of whether CCS can significantly contribute to a deep cut in global CO2 emissions. This paper presents an analysis of the economic and climatic implications of the large-scale use of CCS for reaching a stringent climate change control target, when geological CO2 leakage is accounted for. The natural scientific uncertainties regarding the rates of possible leakage of CO2 from geological reservoirs are likely to remain large for a long time to come. We present a qualitative description, a concise analytical inspection, as well as a more detailed integrated assessment model, proffering insight into the economics of geological CO2 storage and leakage. Our model represents three main CO2 emission reduction options: energy savings, a carbon to non-carbon energy transition and the use of CCS. We find CCS to remain a valuable option even with CO2 leakage of a few %/yr, well above the maximum seepage rates that we think are likely from a geo-scientific point of view.
Keywords: H21; Q40; O33; C61; D58; 330; Climate Change; Geological Leakage; CO2 Capture and Storage (CCS); Technological Innovation; Carbon Dioxide Emission Reduction; Klimaveränderung; Luftverunreinigung; Kohlendioxid; Entsorgungstechnik; Geologie